Frequency, geographical distribution and outcomes of pit viper bites in Malaysia consulted to Remote Envenomation Consultancy Services (RECS) from 2017 to 2020. - Reza Murad Qamruddin; Ruth Sabrina Safferi; Zainalabidin Mohamed Ismail; Mohd Shukruddeen Salleh; Muhammad Nadzmi Hadi Abd Hamid; Vera Effa Rezar Frederic Ng; Wan Chee Goh; Ahmad Khaldun Ismail (Public Library of Science (PLoS), 2023)
Not all pit viper species are present in every state of Malaysia and their distribution varies according to altitude. There is limited information on pit viper bite incidence and its geographical distribution. This was a cross-sectional study of confirmed pit viper bite cases referred to Remote Envenomation Consultancy Services (RECS) from January 2017 to December 2020. Data was collected following the approval of institutional research ethics committee. Universal sampling methods were used. Confirmed pit viper bite cases in each state, geographical location and the antivenom used were reported. A total of 523 confirmed pit viper bite injuries occurred over the 4-year study period. The majority were Malaysians, male and young adults. Most were non-occupational related (83.9%) and involved the upper limbs (46.8%). The commonest pit viper species involved was Trimeresurus purpureomaculatus (23.7%). Green pit viper antivenom (GPAV) was the most frequent antivenom used (n = 51) with the majority of patients requiring only one dose (3 vials). This study provides a better appreciation of indigenous pit viper species distribution for each state and reflects the requirement of appropriate antivenom to be stocked in each state or district hospital.